Facts about Sodium - R. Elaine Turner; Isabel Valentin-Oquendo (EDIS)
Revised! FCS8806, a 2-page handout by R. Elaine Turner and Isabel Valentin-Oquendo, provides basic information about sodium in an easy to read format. Published by the UF Department of Family Youth and Community Sciences, March 2010.